Causes and Repercussions of HIV among Seroconcordant Couples in Pakistan - Ume Habiba; Musrat Perveen; Rabbia Arshad (Journal of Management Practices, Humanities and Social Sciences, 2022)
HIV/AIDS was originated as an epidemic from twenty century in Pakistan. At present, approximately 240,000 individuals have been estimated living with HIV in Pakistan. The current research paper aimed to study the reasons behind the HIV among married couples and investigate the consequences of HIV faced by couples after revealing their HIV status. The present research has utilized social phenomenology by Alfred Schutz (1932) and looking glass self by Cooley (1902). The present research employed phenomenology as qualitative research design. The purposive sampling technique has been utilized to select 15 HIV couples from PIMS Hospital treatment center. The researcher has utilized an in-depth interview guide as a tool to collect the data from the field. Thematic analysis was utilized to interpret the interviews of the participants. The researchers have considered only two themes such as, dynamics of HIV propagation and repercussions of HIV Disclosure. This research will contribute in Academia in this regard as there no study was conducted on the issues and challenges of HIV concordant couples within the Pakistani society. So this research have highlighted the cause and consequence of HIV in couples. Furthermore, HIV individuals needs the social vaccine for their stable social standing.